The importance to financial information in the decision-making process in company’s family structure - Santos, Joana Patrícia Friães (2018)
In Portugal, most enterprises have a family pattern and an important role. Its importance is recognized and justifies the option to develop this research, which aims to determine whether these enterprises assign importance to financial information in the decision-making process. The work allowed gathering enough evidence to conclude on the importance of financial statements for the decision-making process, in particular as regards the use of the balance sheet and income statement. It was also concluded that financial information is primarily used to assess the financial impact, support the current management, investment decisions and comply with tax obligations.